Pemanfaatan Hasil Pertanian Masyarakat Menjadi Produk Sebagai Oleh Untuk Meningkatkan Perekonomian Masyarakat Desa Di Kecamatan Denai Lama Kecamatan Pantai Labu Kabupaten Deli Serdang - Trisnawaty Trisnawaty; Jerry Wilson; Sofi Firani (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
Denai Lama tourist village is the first tourist village in Deli Serdang Regency. This tourist village was formed by involving the local village government and stakeholders to build a new tourism image in Deli Serdang Regency. The Denai Lama tourist village started on January 20, 2019 but before it was inaugurated there were already tourists visiting there. From the results of the research carried out there were 3 important information, including community responses, namely From the number of families in the village of Denai Lama as many as 921 families who have agricultural land as many as 601 families or 65.25 percent and those who do not have agricultural land 320 families or 34.74 percent who own agricultural land. The community believes that good agricultural products sold before and after being processed really help their economy, especially after the Denai Lama village was officially appointed as a tourist village in April 2022 by the Regent of Deli Serdang. The response of the local government is that currently there are more than 97 families managing small and medium enterprises (MSMEs) and 68% of the community as farmers. From the results they have they are greatly helped because the community is able to process the results of ready-to-eat food products and souvenirs for tourists visiting the tourist village of Denai Lama. The response of tourists is that tourists who visit are very interested in visiting the Denai Lama tourist village because they can enjoy the village atmosphere directly and can enjoy the arts and cultural performances provided and can also enjoy processed products from the available community. The tourist attractions provided are quite entertaining with clean huts in the middle of beautiful rice fields and it is fun to spoil the eyes seeing the vast rice fields accompanied by artistic and cultural performances from the village community of Denai Lama.